Buerger's disease: early detection to minimize progression - Santosa, Agus; Ratri, Ritma; Surtiningsih, Surtiningsih (MEDISAINS, 2022)
Background: Delays in the diagnosis of Buerger's disease are common. Its rare cases and lack of information about risk factors and signs and symptoms of the disease are thought to be the causes. This study aims to report and discuss findings of delays in the diagnosis of Buerger's disease cases experienced by two patients over many years.Case presentation: we report two cases of male patients aged 58 and 60 with a long history of smoking at a young age. Both complained of the same symptoms: pain in the tips of the fingers and toes and unhealed wounds. They have suffered from them for years with a history of repeated treatments and got various diagnoses.Conclusion: A comprehensive medical history, supportive physical examination, and angiography diagnostic can prevent delays in diagnosing Buerger's disease and thus minimize disease progression.